A ANALISIS PERSEPSI MASYARAKAT TERHADAP PT. KALTIM JAYA BARA DI LONG – LANUK KECAMATAN SAMBALIUNG: ANALISIS PERSEPSI MASYARAKAT TERHADAP PT. KALTIM JAYA BARA DI LONG – LANUK KECAMATAN SAMBALIUNG - Lisa Puspitasari (Prodi Ekonomi Pembangunan, Universitas Muhammadiyah Berau, 2018)
The purpose of research conducted is to obtain a picture of the perceptions and expectations of society against PT. Kaltim Jaya Bara in Long-Lanuk Sambaliung District, from economic aspect, social aspect, and public welfare aspect. The analysis tools used are IKM (Satisfaction Index). Where IKM is calculated by using